Energy efficient homes for dummies - DeGunther, Rik, 1956- (Hoboken, N.J. : Wiley publishing, 2008)
A practical guide packed with tips and projects for increasing your home's energy efficiency while reducing costs and cutting down on waste and pollution.
Solving the world's problems from your front porch -- Reducing inefficiencies throughout your home -- Putting alternative energy sources to work for you -- Considering efficiency when you buy, build, or sell a home -- The part of tens.
Includes index.
Keywords: Dwellings -- Energy conservation